Utilization of Digital Marketing by Sharia Economics Students at UIN Raden Intan in Online Business - Fida Abdurrofi; Ulil Albab; Mawardi Mawardi; Sri Choiriyati (ProBisnis : Jurnal Manajemen, 2023)
Irresponsible individuals often misuse social media, but for university students, social media is essential, especially for online businesses. Students use derivatives from digital marketing, namely social media, which is supported by various applications for online business purposes. The methodology employed is descriptive qualitative research, and the data sources are primarily gathered through field research and supplemented by observations, interviews, and documentation. The data analysis technique used is qualitative research with a discourse analysis model. Discourse analysis primarily examines the "how" aspect of communication texts or messages. The discourse analysis focuses on analyzing the news text and understanding how the message is conveyed. The utilization of social media, which stems from digital marketing, is predominantly practiced by UIN Raden Intan students engaged in online businesses. They extensively employ social media to advance their business while recognizing the potential risks associated with social media and understanding its various aspects to prevent any detrimental outcomes.